Prevalence and genotype distribution of HPV:a retrospective analysis of 3 014 cases - Shui-feng LI; Si-han LU; Jian-qun DU; Li-ya LI; Qiong-xian WU; Qi-xian XU; Hui-min YANG (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2019)
Objective: To determine the prevalence and genotype distribution of HPV in Guangzhou in last year in order to provide the latest evidence for the prevention and treatment of HPV infection. Methods: HPV types and their correlations with gender, age and HIV were retrospectively analyzed in 3 014 samples from our hospital from January to December, 2018. Results: A total of 3 014 patients, including 730 (24.22%) males and 2 284 (75.78%) females, were included in the analysis. Common types were HPV6, 11, 16, 52 and 58, accounting for 8.36% (252/3014), 7.83% (236/3014), 6.74% (203/3014), 5.97% (180/3014) and 4.64% (140/3014), respectively. In males, 67.81% (495/730) were HPV positive (P<0.001 vs. females). Positive rates of low-risk, high-risk and simple low-risk HPV were 53.29% (389/730), 45.75% (334/730) and 22.05% (161/730), respectively (all P<0.001 vs. females). However, the positive rates of simple high-risk HPV did not differ significantly between males and females (P>0.05). Higher positive rates of HPV were found in age groups of 15~24 and 65~74 years, depicting a trend of "U" shape over age groups. Among 345 out of 3 014 patients with HIV positive, 84.06% (290/345) were HPV positive (P<0.001 vs. overall HPV patients); Positive rates of low-risk, high-risk and simple low-risk HPV were 64.35% (222/345), 66.96% (231/345), and 17.10% (59/345) respectively (all P<0.001 vs. overall HPV patients). But positive rate of simple high-risk HPV did not differ significantly between HIV-infected and overall HPV patients (P>0.05). Conclusions: The most common types of HPV in Guangzhou are HPV 6, 11, 16, 52 and 58 in the last year. The prevalence of HPV is related to gender, age and HIV infection. Strengthening the prevention and treatment of HIV infection are critical for reduction of the HPV infection in Guangzhou.